Gugatan di Pengadilan TUN Terkait Keabsahan SK Caretaker Ketua RT oleh Lurah (Studi Perkara No.xxx/G/2022/PTUN.Jkt) - Prihatin, Onytra Nirwana; Wagiman, Wagiman (Multidisciplinary Journal of Education , Economic and Culture, 2023)
The study began with the RT selection process, which was suspected of cheating, namely the circulation of 'domicile blanks that were suspected to have been signed' by the person who served as the Head of the Village Government Section who was also the Chairperson of the RT Election Committee to vote in the election of the local RT leader. Then the RT selection process took place smoothly and the RT head was elected. The purpose of this research is to determine the position of the caretaker in the perspective of administrative law, and the legality of the Caretaker SK issued by the Lurah according to Administrative Law. This study uses the normative juridical method, using primary legal material, in the form of a decision of the Jakarta State Administrative Court (TUN), No.160/G/2022/PTUN.JKT dated July 14, 2022. The results of the study obtained, Decree or Caretaker Decree or SK Caretaker who Published by the local village head according to law. The candidate who had lost, has carried out objection procedures, by reporting to the "superiors" of the committee chairman, namely the Lurah. Because the objection was not responded to, then the losing candidate filed a lawsuit to the TUN court. The verdict, the judge rejected the entire lawsuit, with the consideration that the Caretaker Decree issued was the authority of the Lurah, even if there were suggestions from the Provincial Government Bureau for re-election. The plaintiff, then submitted an appeal of the TUN High Court, on the grounds that the Lurah had issued a Caretaker SK by backdate. The appeal trial is still ongoing until this research is carried out.